ANALISIS HEDONIC SHOPPING MOTIVATION MASYARAKAT MENGGUNAKAN DOMPET DIIGITAL SHOPEE PAYLATER DALAM PERSPEKTIF SYARIAH - Niken Rika Saputri; Sandra Dewi (CV. Adiba Aisha Amira, 2024)
This thesis was written by Niken Rika Saputri, Nim 3320034 Student of the Sharia Banking Bachelor's Study Program, Faculty of Economics and Islamic Business, Bukittinggi State Islamic University. With the title